Os sistemas agroflorestais no Brasil : abordagem conceitual, ecológica e socioeconômica - Martinelli, João Victor (2020)
Agroforestry systems (AFS) constitute a series of arrangements that integrate the agricultural component, the forest component, and possibly the animal, in consortium, rotational and/or successional combinations. The objective of this research was to map and characterize the SAFs in Brazil, regarding: the frequency and thematic profile of specialized scientific production; the identification of simple and biodiverse systems and the species that compose them; the regional and cultural distinctions of Brazilian agroforestry; and factors related to their comparative economic performance. A systematic review was conducted in the Web of Science database, with a preliminary analysis of 662 articles, and 416 effectively used, published between 1982 and August 2019. Scientific research in AFS is increasing in Brazil, and occurred mainly in the Atlantic Forest, in the Amazon, and in the Northeast, North and Southeast regions. Simple AFS were more numerous than biodiverse ones, and it is presumed that the effectiveness of recent public policies has influenced this outcome. Bahia was the state with the largest number of rural establishments with AFS, and the highest occurrence of research. The most researched topics in Brazil addressed "soil variables", "productivity and development", "fauna", and "biodiversity and ecosystem services", with the first two predominating in simple AFS, and the last two in biodiverse AFS. The most species-rich AFS were more frequent on small properties. Of the majority native, perennial and arboreal, 89% of the 1,010 reported species were cited up to 10 times in the articles. The species for human food use totaled 292, the main edible part of which were fruits. The majority of species present in Brazilian AFS (75%) have not yet been evaluated with respect to the threat of extinction. Brazilian AFS are referred to by several names, have many configurations, in addition to regionally distinctive cultural aspects. Both simple and biodiverse AFS, as integrated production systems, have generally proved to be more economically advantageous than conventional ones. Given the number of properties with AFS in Brazil, the diversity of arrangements and contexts found, and the scope of the mapping carried out here, it was hypothesized that an increase in research is a necessary condition for the development of a definitive profile of Brazilian AFS. The general definition of AFS by IBGE in the Agricultural Census assumes very different production systems as synonyms. For this reason, the inclusion of more details in official surveys would make it possible to obtain advanced information on how farmers conduct their management. One of the growing themes in AFS surveys at the global level is climate change, however, in Brazil this area represented only 2% of the articles. With widespread use in the world and expanding in Brazil, it is a mode of production that contemplates ecosystemic, socioeconomic and climatic benefits.